QUALITY OF CONSTRUCTION PROJECT INTERNSHIP LEARNING THROUGH CUSTOMER SATISFICATION INDEX (CSI) MEASUREMENT AND IMPORTANT-PERFORMANCE ANALYSIS - Fahmy Hermawan; Popi Puspitasari; Julia Damayanti; Lisa Oksri Nelfia; Endah Kurniyaningrum; Giraldi Fardiaz Kuswanda (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2021)
Link and match between the world of business—industry and the flexibility—adaptability to rapid changes in the future, aresome of the reasons why higher education equipped with the Merdeka Belajar-Kampus Merdeka or MBKM system isnecessary. Internshipis one of the MBKM programs, which provides opportunities for students to gain professional work experience in the business world or industry. Civil Engineering Study Program, Universitas Trisakti is organizing an Internship program on Construction Projects in the Odd semester of 2021/2022 academic year. This study is an attempt to share knowledge about stake holder perceptions (students, lecturers, staff, and cooperation partners) regarding the success and failure of the implementation of MBKM. The measurement was based on the priority and satisfaction levels, with the variables of educational infrastructure, reliability, responsiveness, empathy, treatment of students and information systems. This is a quantitative descriptive study using a questionnaire distributed to 217 students, 26 permanent lecturers and 12 civil engineering administration staff as respondents. Cartesian diagram Importance Performance Analysis (IPA) is used to map the value of Customer Satisfaction Index (CSI) which shows the level of stakeholde rsatisfactions. The results show that the CSI values (satisfaction level) areas follows: students has reached 75.67% as itisforadministration staff75.15%, where as lecturers show a quite higher level which is 81.75%. In order to develop a well-organized MBKM in the future, institutions need to establish and manage programs interms of : coordinating between lecturers and field supervisors, adjusting field course Materials to student needs, socializing the amount of MBKM funds to students participating ininternships, and organizing remedial mechanisms. Based on the data analysis,100% of cooperating partners support the continuation of MBKM program and propose that qualified apprentices would become employees in their companies. Keywords: Construction Project, Internship Learning, Customer Satisfaction Index, Important-Performance Analysis.